Characterization of single layer anti-reflective coatings for bolometer-based rare event searches. (18th September 2017) - Hansen, E.V.; DePorzio, N.; Winslow, L.
Abstract: Combining analysis from phonon signals and photon signals is a powerful technique for reducing backgrounds in bolometer-based rare event searches. Anti-reflective coatings can significantly increase the performance of the secondary light-sensing bolometer in these experiments. As a first step toward these improvements, coatings of SiO 2, HfO 2, and TiO 2 on Ge and Si wafers were fabricated and characterized at room temperature and multiple angles of incidence.